GRAPHIC AND PROMOTIONAL VIDEOS MEDIA DESIGN FOR SANCTUARIES IN UDON-THANI MUNICIPAL DISTRICT THROUGH A MODERN CONSERVATIVE APPROACH DESIGNING APPROACH - Wiangyang, Piyaphat; Hanchanawong, Ongart; Songpanya, Mariya (Fine Arts Journal: Srinakharinwirot University, 2025)
Background and Objectives: From the policy of promoting spiritual tourism, a research project has been developed to study the design of graphic media and public relations videos of Sanctuaries in Udon Thani Municipality to promote tourism using modern conservation approaches. Methods: The research used a selection of locations from 5 trusted travel recommendation websites and in-depth interviews with three experts: experts on sacred sites in Udon Thani Municipality, experts in graphic media design, and experts in video design, leading to the creation of modern media. Satisfaction was assessed using questionnaires and interviews with 100 tourists and residents in Udon Thani Municipality. Key Findings: The research results found that 1) Content that promotes tourism to sacred places is the connection to ancestors, important figures in the past, or gods, which will receive the most attention. Next in line are common issues such as health, love, finances, and education, and even unique ways of making wishes that affect the perception of the target group, such as setting a path to make wishes, holding your breath while making wishes, running to fulfill a vow, offering things in pairs, and combining the power of two sacred objects such as the Ganesha and the Naga. The presentation method is therefore an important part that promotes tourism. 2) The graphic design uses a minimalist cut-down style. and uses beige or earth tones to reduce the intimidation, along with a video that presents a route connecting the worship points of the 7 sacred places through modern media in the form of Vlog, broadcasted on TikTok in 7 short episodes and combined into 1 long episode on YouTube. In the area of ​​modern online media, the graphic is like an imprint of contemporaryness superimposed on images of ancient places, antiques with traces of changes over time, and objects of worship. Implications of the Study: Creating Creative Awareness is a modern conservation approaches that emphasize contemporary emotional values ​​on traditional beliefs. In other words, it creates a new perception of the importance of what remains from the past. Conclusions and Future Study: Ancient sites or sacred places are inextricably linked to the way of life and history of the area. Therefore, the creation of new approaches should be a study that builds on the basic concept of conservation.